Perceptions of commercialization activities of research results among academic researchers in Malaysia - Yaacob, Noorulsadiqin; Md Rasli, Amran; Amat Senin, Aslan; Othman, Siti Norezam (Science Publications, 2011)
Problem statement: This study discusses the results of a survey conducted on academic researchers working on biotechnology related research from four leading research universities in Malaysia. The analyses used in this study are essentially exploratory and broadly seeks to address the research question of interest, i.e., to document any differences in opinion between demographic backgrounds group. Approach: Factor analysis and reliability tests were conducted to identify dimensions of commercialization activities and to determine statistical reliability of the dimensions. Subsequently, a series of one-way ANOVA tests were conducted to examine whether perceptions on commercialization activities results differ based on the demographic background of the researchers.Results: The result of this study revealed significant differences in perceptions on commercialization initiatives particularly with regards to years of research experience, experience as administrator/top level management at university level and job status. Conclusion/Recommendation: Qualitative studies were recommended to complement this exploratory study.